Visual clinical diagnosis of jaundice on normal birthweight infant in Dr. Sardjito hospital Yogyakarta - Satyawati, Satyawati (Universitas Gadjah Mada, 2002)
Background: Neonatal jaundice is a problem commonly faced by health workers. The visual assessment of jaundice is very subjective and less accurate. Simplified body surface classification is expected to make the assessment easier and more accurate.Objective: To determine diagnostic accuracy of jaundice established visually using a simpler classification.Material and methods: This is an observational cross sectional diagnostic test. The study was performed in Maternal Perinatal Installation Dr. Sardjito Hospital in August 1st - October 31st 2002. Result: The interobserver agreement on jaundice was good (kappa = 0,6) the agreement on jaundice based on body area was good (weighted kappa = 0.75). The median of serum bilirubin level was 1) Face 5.8 mg/dL; 2) Abdomen 10.1 mg/dL; 3) Arms and legs 14 mg/dL; 4) Palms and soles 17.6 mg/dL. Based on 95th percentile serum bilirubin level as cut off point, the sensitivity and specificity was 1) Face 2% (95% CI: 0.1 - 12.2%) and 29% (95% CI :14.9 - 48.2%); 2) Abdomen 5.3 % (95% CI: 0.3 - 28.1%) and 57.4 % (95% CI 44.1 - 69.7%); 3) Arms and legs 33.3 % (95% CI:1,8 - 87.5%) and 70.1% (95% CI: 58.5 - 79.8%) 4) Palms and soles 100 % (95% CI: 5.5 - 100%) and 93.7 % (95%Cl: 85.2 - 97.6%) Conclusion: Simplified visual assessment of the grade of jaundice can not be applied as a diagnostic method for jaundice assessment.Key words: visual assessment - jaundice on normal birthweight - simplified body surface classification.